EVALUASI PROGRAM JEJAK SERIBU PRENEUR DALAM KEGIATAN PENGOLAHAN MAKANAN OLEH-OLEH DI KELURAHAN PULAU TIDUNG - Fithri Farhana; Wg. Pramita Ratnasari (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2021)
Jejak SeribuPreneur is a community development program implemented in the Village of Tidung Island, Thousand Islands, DKI Jakarta. Jejak Seribu Preneur program aims to develop the business of members of the target group by making various improvements, including financial capital improvement, physical capital improvement and human resources capital improvement. One of the stages of community development activities is the evaluation stage, where the function of the evaluation stage to see the success of the program, in this case the Jejak Seribu Preneur program. This study uses evaluation model according to Pietrzak, et al., where according to him there are three stages of evaluation, namely input evaluation, process evaluation and results evaluation. This study uses qualitative approach with descriptive research type, where researchers will describe what it is related to the findings of the study based on observations, interviews, documentation and literature. This research aims to find out the planning, implementation and results of the Jejak Seribu Preneur program in Tidung Island Village. The result of this research is the success of the Jejak Seribu Preneur program in developing the business of members of the target group, this can be seen from the differences, namely the increase in revenue, the increase in science and knowledge, and the expanding sales market.